Sulphur dioxid induced hematotoxicity and its melioration by emblicaofficinalis in rattusnorvegicus (berkenhout) - Dr.MADHURI YADAV, (International Journal of Pharma and Bio Sciences, 2016)
Present study was designed to investigate the adverse effects of SO2 on hematology in terms of total leucocyte count [TLC] and differential leucocyte count [DLC] – monocyte count, lymphocyte count, neutrophil count, basophil count and eosinophil count, besides, modulatory effects of Emblica officinalis (Amla) in albino rat. The rats of both sexes were kept in standard laboratory conditions and grouped as- control group (1) kept away from exposed rats for 30 & 60 days, experimental group (2) exposed to 80ppm SO2 gas (1h/d) for 30 & 60 days and experimental group (3) exposed to 80ppm SO2 gas (1h/d) with oral supplementation of aqueous extract of Emblica officinalis (200mg/rat/day) for 30 & 60 days. The findings of the present study showed a significant increase in total leucocyte count, besides, decrease in differential leucocyte count with an increase in neutrophil count is the result of inflammation due to toxic action of SO2 gas. However, SO2 induced alterations were meliorated after supplementation of aqueous extract of Emblica officinalis due to its antioxidant and anti-inflammatory activity, in albino rats.